Low-temperature CO oxidation on multicomponent gold based catalysts - Ramirez Reina, Tomas; Ivanova, Svetlana; Centeno, Miguel Angel; Odriozola, Jose Antonio (Frontiers in Chemistry, 2013)
In this work the development of gold catalysts, essentially based on γ-alumina with small superficial fraction of Ce-Fe mixed oxides as support for the low temperature CO oxidation is proposed. Characterization results obtained by means of XPS, UV-Vis spectroscopy and H2-TPR are employed to correlate the activity data with the catalysts composition. The bare γ-alumina supported gold catalyst demonstrates the poorest activity within the series. The addition of CeO2 or FeOX improves the catalytic performance, especially observed for the CeO2-FeOx mixed oxide doped samples. This enhanced CO oxidation activity was related to the Ce-Fe interaction producing materials with promoted redox properties and therefore oxidation activity